Low 2016/17 season vaccine effectiveness against hospitalised influenza A(H3N2) among elderly: awareness warranted for 2017/18 season - Rondy, Marc (2017)
In a multicentre European hospital study we measured influenza vaccine effectiveness (IVE) against A(H3N2) in 2016/17. Adjusted IVE was 17% (95% confidence interval (CI): 1 to 31) overall; 25% (95% CI: 2 to 43) among 65-79-year-olds and 13% (95% CI: -15 to 30) among those ≥ 80 years. As the A(H3N2) vaccine component has not changed for 2017/18, physicians and public health experts should be aware that IVE could be low where A(H3N2) viruses predominate.